Monitoring healthcare-associated infections and antimicrobial use at regional level through repeated point prevalence surveys: what can be learnt?. Issue 4 (April 2019) - Arnoldo, L.; Smaniotto, C.; Celotto, D.; Brunelli, L.; Cocconi, R.; Tignonsini, D.; Faruzzo, A.; Brusaferro, S.; ,
Summary: Background: Healthcare-associated infections (HAIs) surveillance is an essential part of any infection prevention and control programme. Repeated point prevalence surveys (PPSs) according to European Centre for Disease Prevention and Control (ECDC) protocol have been implemented in all Friuli Venezia Giulia (FVG) region (Italy) acute hospitals to reduce and control HAIs. Aim: Using the repeated PPSs within a regional-healthcare system (RHS) to promote and evaluate infection prevention and control (IPC) programmes. Methods: The standard versions of the ECDC PPS protocols were used in all four surveys (2011, 2013, 2015, 2017). All RHS public and private accredited hospitals were involved within the 'safe care network' programme. Findings: The numbers ofs urveyed patients in the four PPSs were 3172, 3253, 2969 and 3036, respectively. Prevalence of HAIs and antimicrobial use (AU) decreased significantly from 2011: HAIs ( P <0.05) 7.1%, 6.3%, 5.5%, 5.8% and AU ( P <0.01) 40.4%, 39.2%, 36.0%, 37.2%, respectively. The appropriateness of duration of surgical prophylaxis increased significantly (<24 h increased through surveys related to one in 2011: odds ratio (OR), 95% confidence interval (CI) 1.29, 0.92–1.81; 1.95, 1.31–2.91; 1.78, 1.20–2.64, respectively). The most frequently detected HAIs were: bloodstream, urinary tract, pneumonia and surgical site (more than the 70% of HAIs in each PPS). Conclusion: The FVG regional approach to HAIs and AU surveillance was able to contribute to reduce prevalence over a 7-year period. Furthermore, it was able to keep hospital attention on HAIs and AU through the years and to guarantee a standardized and comparable evaluation of HAIs and AU burden in all RHS hospitals, as well as impacting on HAIs and AU regional programmes.